2015
DOI: 10.1093/mnras/stv928
|View full text |Cite
|
Sign up to set email alerts
|

G2C2 – IV. A novel approach to study the radial distributions of multiple populations in Galactic globular clusters

Abstract: We use the HB morphology of 48 Galactic GCs to study the radial distributions of the different stellar populations known to exist in globular clusters. Assuming that the (extremely) blue HB stars correspond to stars enriched in Helium and light elements, we compare the radial distributions of stars selected according to colour on the HB to trace the distribution of the secondary stellar populations in globular clusters. Unlike other cases, our data show that the populations are well mixed in 80% of the cases s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 65 publications
(91 reference statements)
4
31
2
Order By: Relevance
“…This work is sensitive to a similar radial range to our surface brightness profiles, from around the core/half-light radius to a few half light radii. Vanderbeke et al (2015) drew similar conclusions to our surface brightness profiles of M 31's globular clusters, with 80% of their Galactic globular cluster sample having similarly distributed HB stars. Some of the remaining clusters did show centrally concentrated extreme HB populations, while they were less concentrated in three of the clusters.…”
Section: Distribution Of Blue/ Extreme Hb Starssupporting
confidence: 75%
See 2 more Smart Citations
“…This work is sensitive to a similar radial range to our surface brightness profiles, from around the core/half-light radius to a few half light radii. Vanderbeke et al (2015) drew similar conclusions to our surface brightness profiles of M 31's globular clusters, with 80% of their Galactic globular cluster sample having similarly distributed HB stars. Some of the remaining clusters did show centrally concentrated extreme HB populations, while they were less concentrated in three of the clusters.…”
Section: Distribution Of Blue/ Extreme Hb Starssupporting
confidence: 75%
“…However, the distribution of the resolved HB populations have been studied in some of these clusters (e.g. Iannicola et al 2009;Vanderbeke et al 2015). Vanderbeke et al (2015) recently traced the radial distribution of red, blue and extreme HB stars in 48 Galactic globular clusters, by identifying the populations in ground based optical g− and z−band photometry.…”
Section: Distribution Of Blue/ Extreme Hb Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of nine GCs using the SDSS database by L11 suggested that seven of those Galactic GCs (M2, M3, M5, M13, M15, M53, & M92) have a centralized concentration of enriched stars. Although consistent with the qualitative picture, these results are seemingly at odds with numerous later studies (Larsen et al 2015;Vanderbeke et al 2015;Massari et al 2016;Lee 2017;Nardiello et al 2018a;Savino et al 2018;Smolinski et al 2020). The identification of a centralized enriched population is not unique to L11; such results have also been reported by others (e.g.…”
Section: Introductionsupporting
confidence: 58%
“…For example, several earlier papers found that a large fraction of clusters tended to have centrally concentrated second-generation populations (e.g., Carretta et al 2009bCarretta et al , 2010aKravtsov et al 2011;Lardo et al 2011;Nataf et al 2011;Johnson & Pilachowski 2012;Milone et al 2012b;Richer et al 2013;Cordero et al 2014;Massari et al 2016;Simioni et al 2016). However, similar studies have also argued either that many clusters have no radial gradient (e.g., Iannicola et al 2009;Lardo et al 2011;Milone et al 2013;Dalessandro et al 2014;Cordero et al 2015;Nardiello et al 2015;Vanderbeke et al 2015) or that the first-generation stars are actually the most centrally concentrated (e.g., Larsen et al 2015;Vanderbeke et al 2015;Lim et al 2016). Although the measurements are typically straightforward, biases can be introduced because clusters are at different stages in their dynamical evolution and various studies frequently sample different cluster regions.…”
Section: Spatial Mixing Of First-and Second-generation Starsmentioning
confidence: 99%